Design, Fabrication and Analysis of Material Requirements of Spices Mixing Machine - Rozi Saferi; Asmara Yanto; Jendri Surianda (LP2M - Institut Teknologi Padang, 2020)
The process of mixing the spices often done manually, which it takes time and reduces the effectiveness of the process. This study aims to analyze the design, material requirements and production process of a spices mixer machine. In this work is also done to analyze the speed optimization in mixing process of spices with the main food. Analysis of the machine design using the finite element method by aided Autodesk Inventor software. The analysis results show that the mass density of the frame is 8.8041 g/cm3, and the maximum compressive strength is 345 MPa. Furthermore, the young’s modulus is 200 GPa, the position ratio is 0.3 and the shear modulus is 76.9231 GPa. The test of spices mixer machine showed that the optimal spice stirring value occurred at 35 rpm with a mixing percentage of 83%.The process of mixing the spices often done manually, which it takes time and reduces the effectiveness of the process. This study aims to analyze the design, material requirements and production process of a spices mixer machine. In this work is also done to analyze the speed optimization in mixing process of spices with the main food. Analysis of the machine design using the finite element method by aided Autodesk Inventor software. The analysis results show that the mass density of the frame is 8.8041 g/cm3, and the maximum compressive strength is 345 MPa. Furthermore, the young’s modulus is 200 GPa, the position ratio is 0.3 and the shear modulus is 76.9231 GPa. The test of spices mixer machine showed that the optimal spice stirring value occurred at 35 rpm with a mixing percentage of 83%.